OP0057 Monocyte chemoattractant protein 1 is expressed from kidney epithelial cells in response to activated macrophages in juvenile-onset systemic lupus erythematosus (JSLE). (23rd January 2014) - Watson, L.; Midgley, A.; Ballantine, L.; Jones, C.A.; Holt, R.C.; Marks, S.D.; Pilkington, C.; Tullus, K.; Beresford, M.W.
Abstract : Background: JSLE is a severe autoimmune condition where up to 70% develop renal involvement and a small number will progress to established renal failure (1). Current methods of diagnosing active lupus nephritis (LN) include the renal biopsy and urine protein quantification. The renal biopsy is an invasive procedure and poses risks. We have previously identified increased urine concentrations of monocyte chemo-attractant protein 1 (MCP1) in children with active LN compared to inactive LN or healthy controls (2), which may act as a novel biomarker. The glomerular expression of MCP1 has been linked with a worse renal prognosis (3). Objectives: We aimed to determine whether podocyte (kidney epithelial) cells are responsible for increased expression of the biomarker MCP1 in patients with active LN. Methods: Monocytes were isolated and cultured to become monocyte-derived macrophages (inactive) then incubated with recombinant IFNγ 1ng/ml for 48 hours (activated macrophages). An in vitro model of LN was developed using a human podocyte cell line (4). Podocytes were cultured in the presence of the media from either inactivated or activated macrophages. Protein and mRNA expression of MCP1 in the podocytes were quantified and mRNA normalised to 18s. Results are expressed as mean concentration ± standard deviation. The study had ethical approval and parental/patient consent/assent. Results: Podocyte MCP1 protein concentration were statistically significantly increased following incubation with activated macrophage media (4.09×10 4 ±0.5×10 4 pg/ml) compared to podocytes incubated with inactivated macrophage media (2.73×10 4 ±0.58×10 4 pg/ml, p<0.05). Podocyte MCP1 relative mRNA expression was also statistically significantly increased in the cells exposed to activated macrophage media (activated media 8.87×10 -3 ±1.3×10 -3 ) when compared to inactivated media (1.29×10 -3 ±0.9×10 -3 ; p<0.01). Conclusions: In active lupus nephritis the macrophages are one of the first inflammatory cells to enter the kidney, they then initiate an inflammatory cascade. The presence of MCP1 in JSLE renal histology is associated with severe lupus nephritis (3). We have demonstrated that the podocyte cell is able to up regulate protein and gene expression of MCP1 following stimulation with activated macrophage media. MCP1 can originate from the kidney epithelial cells and may contribute to the increased concentration of urinary MCP1 seen in patients with active lupus nephritis. References: [1] Baqi N, Moazami S, Singh A, Ahmad H, Balachandra S, Tejani A. J Am Soc Nephrol. 1996 Jun;7(6):924-9. [2] Watson L, et al. Lupus 2011 (in press) [3] Marks SD, Williams SJ, Tullus K, Sebire NJ. Nephrol dial transpl. 2008 Nov;23(11):3521-6. [4] Saleem, M.A., et al., Journal of the American Society of Nephrology: JASN, 2002. 13(3): p. 630-8 Disclosure of Interest: None Declared